The COEQUAL Registry: Creating Opportunities to Increase Health Equity & Equality for Persons at Risk for AD/ADRD. (20th December 2022) - Balls‐Berry, Joyce E; Mozersky, Jessica; Postman, Whitney; Denny, Andrea; Xiong, Chengjie; Kannampallil, Thomas; Thompson, Vetta Sanders; Hassenstab, Jason J.; Gabel, Matthew; Hill, Carl V.; Saunders, John; O'Leary, Catina; et al.
Abstract: Background: Communities with the highest disease burden from Alzheimer's disease and related dementias (ADRD) often experience considerable health disparities. These disparities are due to systematic and structural racism, classism, ageism, and social determinants of health, leading to distrust of and lower engagement with biomedical research. These injustices exacerbate disparities, ultimately leading to less generalizability of research findings. Therefore, we hypothesized that creating a culturally appropriate ADRD research registry called COEQUAL would increase underrepresented communities' engagement in ADRD research. Methods: Our NIH‐funded community and patient‐engaged study aims to identify and enhance current practices to promote high‐yield engagement and retention of diverse participants in ADRD research in St. Louis, Missouri. Based at the Washington University Knight Alzheimer's Disease Research Center, our partners include Saint Louis University, Wesley House (a social service organization), the Greater Missouri Chapter of the Alzheimer's Association, and Health Literacy Media. We have a 20‐member Governance Board to create a culturally appropriate research registry. Before creating the COEQUAL registry, we plan to conduct a community needs assessment with listening sessions and a pre/posttest survey of n = 160 community members, patients, caregivers, and healthcare providers aged 45+. We will use direct/indirect recruitment methods like posts in the health system patient portal, social media, and emails/mailers to recruit participants. Our facilitator's guide and a pre/posttest survey will contain validated and culturally appropriate items to gauge perceptions, practices, and knowledge related to ADRD, willingness to participate in an ADRD research registry, and ways to engage and retain diverse participants. We will oversample participants who self‐identify as Black (African American, African, African Caribbean, or African Ancestry). Findings from the community needs assessment will be used to inform recruitment, ongoing engagement with, and retention of, individuals in ADRD research. Result: We anticipate gaining knowledge of the perceptions and practices of engaging community members, patients, and providers in creating a culturally appropriate ADRD research registry. Conclusion: The feasibility of creating a culturally appropriate ADRD research registry in St. Louis is critical to ensure justice and generalizability in research. Moreover, using a community and patient‐engaged research approach increases the cultural appropriateness of ADRD research.